Effects of Water Constituents on Textile Mills Production and Boilers Efficiency, Gezira State, Sudan - Eltayeb, Musa; Abdalla, Mutasim; Mohamed, Babiker (Gezira Journal of Engineering and Applied Sciences, 2019)
Water, the raw material for making steam, contains various types and amounts of impurities. Completely pure water, although desirable for steam generating systems is non-existent. When water is boiled into steam its volume increases about 1600 times, producing a force that is almost as explosive as gunpowder. This causes the boiler to be extremely dangerous equipment that must be treated with utmost care. This paper studied the effects of water constituents on boilers efficiency and textile mill production. Samples of water were collected from two different locations namely from Blue Nile Textile Company and Gematex Textile Company, which are located in the Gezira State, Sudan. Chemical analysis, such as: total dissolved solids (TDS), pH value, electric conductivity (E.C), carbonates (CO 3 -2 ) and bicarbonates (HCO 3 -1 ), calcium ion (Ca +2 ) and temporary hardness were carried out. The obtained results showed that samples of the boiler feed water for the two factories constitute various anions and cations with varying degrees. The boiler may be deficient and the cost of running will be high. It is recommended for more certainty that these constituents should be removed totally from the water. All recommended  processes  in  the  pipe line  to  condition  the  boiler  feed  water  should  be  adopted  and  maintained  perfectly  before the  water  enters  the  boiler  to  avoid  serious  limitations.